THE EFFECT OF COMPREHENSIVE NURSING INTERVENTION ON THE INCIDENCE OF GASTROINTESTINAL COMPLICATIONS AMONG CRITICALLY ILL PATIENTS WITH INTERMITTENT ENTERAL FEEDING - Abd El Rady Mohamed El Sayed; Manar Hamza; Zeinab Hussien Ali (International Journal of Advanced Research, 2026)
Background: Comprehensive nursing intervention reduces gastrointestinal complications in critically ill patients with receiving intermittent enteral feeding by providingComprehensive nursing intervention. Aim: The present studyaimed tostudy the effect of comprehensive nursing intervention on the incidence of gastrointestinal complications among critically ill patients with intermittent enteral feeding. Design:A quasi-experimental design was used. Sitting: The study was conducted at the Electricity Hospital Almaza - Cairo, Egypt. Sample:A purposive sample of 160 adult patients on intermittent enteral feeding was assigned into two equal groups: study and control (80 patients each). The study group received comprehensive nursing intervention while the control group received routine care.